Explanation:
Let's say the rectangle's width is equal to y. We know that the length is three times the width, so the length = 3 * y. We also know that the area for a rectangle is equal to length * width, so the area, z, is equal to
(3*y) * y = z
3 * y² = z
Now, let's increase the width of the rectangle by 1. We can replace y with y+1 (as y+1 is 1 greater than y), and 3 * y with 3 * (y+1) to get
3*(y+1) * (y+1) = new area
(3y+3)*(y+1) = new area
3y²+3y +3 y + 3 = new area
3y² + 6y + 3 = new area
The difference in area is equal to the new area subtracted by the old area, or
3y²+6y+3 - 3y² = 6y +3. The variable for x is not given, so if x = (2y+1), the answer would be the second choice. However, solely using the information given, it is impossible to determine a solution outside of saying that it is not option 4, as 6y + 3 ≠ 3